Canadian Platform for Trials in Noninvasive Brain Stimulation (CanStim) Consensus Recommendations for Repetitive Transcranial Magnetic Stimulation in Upper Extremity Motor Stroke Rehabilitation Trials. (February 2021) - Edwards, Jodi D.; Black, Sandra E.; Boe, Shaun; Boyd, Lara; Chaves, Arthur; Chen, Robert; Dukelow, Sean; Fung, Joyce; Kirton, Adam; Meltzer, Jed; Moussavi, Zahra; Neva, Jason; et al.
Objective . To develop consensus recommendations for the use of repetitive transcranial magnetic stimulation (rTMS) as an adjunct intervention for upper extremity motor recovery in stroke rehabilitation clinical trials. Participants . The Canadian Platform for Trials in Non-Invasive Brain Stimulation (CanStim) convened a multidisciplinary team of clinicians and researchers from institutions across Canada to form the CanStim Consensus Expert Working Group. Consensus Process . Four consensus themes were identified: (1) patient population, (2) rehabilitation interventions, (3) outcome measures, and (4) stimulation parameters. Theme leaders conducted comprehensive evidence reviews for each theme, and during a 2-day Consensus Meeting, the Expert Working Group used a weighted dot-voting consensus procedure to achieve consensus on recommendations for the use of rTMS as an adjunct intervention in motor stroke recovery rehabilitation clinical trials. Results . Based on best available evidence, consensus was achieved for recommendations identifying the target poststroke population, rehabilitation intervention, objective and subjective outcomes, and specific rTMS parameters for rehabilitation trials evaluating the efficacy of rTMS as an adjunct therapy for upper extremity motor stroke recovery. Conclusions . The establishment of the CanStim platform and development of these consensus recommendations is a first step toward the translation of noninvasive brain stimulation technologies from the laboratory to clinic to enhance stroke recovery.